2019
DOI: 10.1080/03081087.2019.1631742
|View full text |Cite
|
Sign up to set email alerts
|

Solvable Leibniz algebras with naturally graded non-Lie p-filiform nilradicals whose maximal complemented space of its nilradical

Abstract: The present article is a part of the study of solvable Leibniz algebras with a given nilradical. In this paper solvable Leibniz algebras, whose nilradicals is naturally graded p-filiform non-Lie Leibniz algebra (n − p ≥ 4) and the complemented space to nilradical has maximal dimension, are described up to isomorphism. Moreover, among obtained algebras we indicate the rigid and complete algebras.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Let us denote by R(N, m) the class of maximal (with respect to the dimension) solvable Leibniz algebras whose nilradical is N , that is, the class of solvable Leibniz algebras whose nilradical is N and maximal possible codimension of the nilradical is m. In [3] it was proved that for the nilpotent Leibniz algebra N = µ 1 the value of m is equal to k and the description of R(µ 1 , k) was given as follows.…”
Section: Definition 22 a Leibniz Algebra L Is Said To Be Complete If ...mentioning
confidence: 99%
“…Let us denote by R(N, m) the class of maximal (with respect to the dimension) solvable Leibniz algebras whose nilradical is N , that is, the class of solvable Leibniz algebras whose nilradical is N and maximal possible codimension of the nilradical is m. In [3] it was proved that for the nilpotent Leibniz algebra N = µ 1 the value of m is equal to k and the description of R(µ 1 , k) was given as follows.…”
Section: Definition 22 a Leibniz Algebra L Is Said To Be Complete If ...mentioning
confidence: 99%
“…Such algebras are also important from a cohomological point of view and many complete Leibniz algebras belong to the class of cohomologically rigid algebras. Later J.K. Adashev and others [3] showed that solvable Leibniz algebra with nilradical being naturally graded p-filiform Leibniz algebra of maximal codimension is complete. Moreover, B.A.…”
Section: Introductionmentioning
confidence: 98%